2015
DOI: 10.1002/cjas.1303
|View full text |Cite
|
Sign up to set email alerts
|

The link between product diversification and performance among Spanish manufacturing firms: Analyzing the role of firm size

Abstract: This study sheds additional light on the product diversification‐performance relationship for firms in a country having recently attained an advanced economy status in our period of analysis. We assume there will be an inverted U‐shaped relationship and use a sample of small, medium, and large Spanish manufacturing firms between 1994 and 2008. Our findings provide solid support for this assumption, and are identical when the sample consists of small, medium, and large firms and of large firms alone. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 107 publications
(245 reference statements)
2
9
0
Order By: Relevance
“…The finding is consistent with previous empirical studies (Boz et al, 2013;Chen and Yu, 2012;Hautz et al, 2013;Yiğit and Tür, 2012). Furthermore, a recent study by Benito-Osorio et al (2015), obtained more solid evidence on this issue. They found the existence of an S-shaped relationship between performance and product diversification using a sample of Spanish manufacturing firms from 1994 to 2008.…”
Section: Tablesupporting
confidence: 92%
“…The finding is consistent with previous empirical studies (Boz et al, 2013;Chen and Yu, 2012;Hautz et al, 2013;Yiğit and Tür, 2012). Furthermore, a recent study by Benito-Osorio et al (2015), obtained more solid evidence on this issue. They found the existence of an S-shaped relationship between performance and product diversification using a sample of Spanish manufacturing firms from 1994 to 2008.…”
Section: Tablesupporting
confidence: 92%
“…This finding is also supported by research of Cagliano et al (2001), Gong et al (2013), Bourlakis et al (2014), Leal-Rodríguez et al (2015), Benito-Osorio et al (2015), Vithessonthi and Tongurai (2015) and others. The size of a firm may be determined by its assets (Smith et al, 2015;Brighi & Venturelli 2014;Schaefer, 1998;Horst, 1972), revenue (Hwang, 2015;Schaefer, 1998;Cohen et al, 1987) market capitalization (Baker & Hall, 2004), number of employees (Bolotova, 2016;Benito-Osorio et al, 2015;Elhamma, 2015;Leal-Rodríguez, 2015;Chenhall, 2003), number of establishments (Bolotova, 2016), alliance portfolio (Lahiri & Narayanan, 2013) and other indicators. For this research, the size classification employed by Statistics Canada is used, which classifies firms having less than 100 employees as small, with 100 to 499 employees as medium and more than 500 employees as large (Statcan, 2018).…”
Section: Size Of Firmsupporting
confidence: 82%
“…Leal-Rodríguez et al (2015) find that firm size has a moderating effect on organizational unlearning on firm's performance. Benito-Osorio et al (2015) analyzed the role of firm size on relationship between product diversification and performance and found that large firms can perform better with a higher level of diversification.…”
Section: Size Of Firmmentioning
confidence: 99%
“…Even though product diversification-organizational performance relationship has a dedicated stream of research, a general consensus regarding the theoretical and empirical lacks [2,6,49] with both linear [6,50,51] and inverted-U relationships [6,[52][53][54].…”
Section: Product Diversification and Organizational Performancementioning
confidence: 99%